PENGARUH PROFESIONALISME, ETIKA PROFESI, INDEPENDENSI, DAN MOTIVASI KERJA PADA KINERJA INTERNAL AUDITOR - Triyanthi, Meylinda; Budiartha, Ketut (E-Jurnal Akuntansi, 2015)
This study aims to determine the effect of professionalism, professional ethics, independence, and motivation on the performance of the internal auditors on a Yamaha dealer in the city of Denpasar. This study was done because of the differences in the ownership and management interests of the company, and therefore the performance of the internal auditors need to be considered for checking and detecting the possibility and the risk incurred by conducting periodic audits and uncover any existing findings. This research was conducted in the entire Yamaha dealer in the city of Denpasar city located in the region include North Denpasar, East Denpasar, West Denpasar, and South Denpasar in 2014 by making the internal auditors as many as 36 people as a sample. Data was coll . ected by d . istributing qu . estionnaires . T . his res . earch u . sing multip . le li . near regre . ssion . Based on the analysis, it is known that the professionalism, professional ethics, independence and motivation positive effect on the performance of the auditor on the Yamaha dealer in the city of Denpasar. Variable professionalism, professional ethics, independence and motivation to contribute as much as 93.6 percent on the performance of the internal auditors.
Keywords: Professionalism, professional ethics, independence, motivation and performance of the internal auditors